Pengaruh Kualitas Produk, Harga dan Promosi terhadap Keputusan Pembelian Sepeda Motor Merek Honda (Studi Kasus di Kecamatan Batu) - Alfiah Alfiah (STIE Kertanegara Malang, 2021)
The market share of Honda motorcycles in Indonesia is currently experiencing a decline. One of the causes that affect the decline in the market share of Honda motorcycles is the decline in buying interest of consumers who have been customers of Honda motorcycles to make repeat purchases. In addition, consumers of new motorcycles are also less interested in buying Honda motorcycles.This study aims to determine the effect of product quality, price and promotion on purchasing decisions for Honda motorcycles in Batu sub-district. The sampling in this study was non-probability sampling using a purposive sampling technique, totaling 40 people in Batu District who had purchased a Honda motorcycle. The data analysis technique in this study used multiple linear regression with the SPSS Version 25.0 program, after going through the instrument test and classical assumption test. The results of the study prove that two independent variables, namely product quality and promotion, have a significant and significant influence on the purchase decision variable for Honda motorcycles, while the price variable does not have a significant influence on respondents in determining the decision to buy a Honda motorcycle. Tests carried out together showed that all independent variables (product quality, price and promotion) had an effect on purchasing decisions. Keywords: Purchase Decision, Product Quality, Price, Promotion